Multipronged Fabrication of Co3Se4 Wrapped into N‐Doped Multiwall Carbon Nanotubes Tangled Hollow Dodecahedron Framework for Overall Water Splitting under Benign Condition. Issue 17 (18th August 2021) - Yang, Xiao; Chen, Tao; Liu, Li; Fu, Wensheng
Abstract: In this work, a synergistic strategy is proposed to synthesize a high‐performance bifunctional electrocatalyst (marked as Co3 Se4 /N‐CNTs) for neutral water splitting, in which Co3 Se4 nanoparticles are wrapped into N‐doped multiwall carbon nanotubes assembled hollow dodecahedron framework. The neutral‐oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) catalytic performances of Co3 Se4 /N‐CNTs are maximally optimized by regulating nanostructure engineering, element doping, and carbon coating. In 1 m phosphate buffer solution (PBS) electrolyte, Co3 Se4 /N‐CNTs catalyst exhibits superior stability and catalytic activity for OER and HER, yielding a geometrical catalytic current density of 10 and −10 mA cm −2 at rather low overpotentials of 385 and 102 mV, respectively, meanwhile operating continuously for 35 h without obvious polarization increase. It is worth mentioning here, when a neutral electrolyzer is assembled, Co3 Se4 /N‐CNTs‖ Co3 Se4 /N‐CNTs cell contributes a high performance for overall water splitting in 1 m PBS electrolyte, delivering a current density of 10 mA cm −2 at a low applied external potential of 1.75 V, and displaying satisfying operation stability without evident deactivation after 35 h. The catalytic performances rival those of catalysts operated under moderate conditions. Consequently, all the merits promise that Co3 Se4 /N‐CNTs is an attractive bifunctional catalyst for hydrogen fuel production and storage of intermittent renewable energy sources under environmentally friendly conditions. Abstract : Herein, a bifunctional Co3 Se4 /N‐CNTs (CNTs = carbon nanotubes) electrocatalyst is designed by a synergistic strategy including nanostructure engineering, element doping, and carbon coating for neutral water splitting.